Struktur dan Fungsi Cerita Rakyat Gadih Basanai pada Masyarakat Surantih - Mayeni, Desri; Juita, Novia; Hamidin, Hamidin (Universitas Negeri Padang, 2013)
The purpose of this research is to describe the structure and function of folklore Gadih Basanai in the Surantih society. Furthermore, the problem in this research is focusing to the structure and function of folklore Gadih Basanai in the Surantih society. This research is kind of qualitatife by using descriptive method. Then, the objects of folklore Gadih Basanai in the Surantih society. The data of the research is collected by using interview technique and observator. Base on the discover the results are: first, characterized, incident, channel, beckgraund, the point of view, thema, and moral value. Second, if found that the function of the story as a tool to educate children, it can be an entertainment or a tool to force obey public rule. Third, in the folklore Gadih Basanai there can be found many fuction of the story that many educate children, keep the promise, obey their parents.